Pólipo fibroepitelial vulvar: una serie de casos - Hernández Martínez, Adela María (2023)
Fibroepithelial polyps are common benign skin tumors in the general population.However, genital tract involvement is unusual. Their etiology is unclear, butassociations with metabolic disorders and hormonal fluctuations have beendescribed, which explains their higher prevalence in women. Due to the variety ofdifferential diagnoses, histopathological evaluation is necessary. Their managementis usually conservative. However, they may require surgical intervention insome cases. We present four cases of vulvar fibroepithelial tumors of differentsizes, one of them classified as giant, as well as the management approach.With this presentation, we hope to improve knowledge, diagnostic accuracy andcontribute to the effective treatment of patients with this rare vulvar pathology.